Differential responses of rabbit ventricular and atrial transient outward current (Ito) to the Ito modulator NS5806. Issue 5 (7th March 2017) - Cheng, Hongwei; Cannell, Mark B.; Hancox, Jules C.
Abstract: Transient outward potassium current (Ito ) in the heart underlies phase 1 repolarization of cardiac action potentials and thereby affects excitation–contraction coupling. Small molecule activators of Ito may therefore offer novel treatments for cardiac dysfunction, including heart failure and atrial fibrillation. NS5806 has been identified as a prototypic activator of canine Ito . This study investigated, for the first time, actions of NS5806 on rabbit atrial and ventricular Ito . Whole cell patch‐clamp recordings of Ito and action potentials were made at physiological temperature from rabbit ventricular and atrial myocytes. 10  μ mol/L NS5806 increased ventricular Ito with a leftward shift in Ito activation and accelerated restitution. At higher concentrations, stimulation of Ito was followed by inhibition. The EC50 for stimulation was 1.6  μ mol/L and inhibition had an IC50 of 40.7  μ mol/L. NS5806 only inhibited atrial Ito (IC50 of 18  μ mol/L) and produced a modest leftward shifts in Ito activation and inactivation, without an effect on restitution. 10  μ mol/L NS5806 shortened ventricular action potential duration (APD) at APD20 ‐APD90 but prolonged atrial APD. NS5806 also reduced atrial AP upstroke and amplitude, consistent with an additional atrio‐selective effect on Na + channels. In contrast to NS5806, flecainide, which discriminates between Kv1.4 and 4.x channels, produced similar levels of inhibition of ventricular and atrial Ito . NS5806 discriminates between rabbit ventricular and atrial Ito, with mixed activator and inhibitor actions on the former and inhibitor actions against the later. NS5806 may be of significant value for pharmacological interrogation of regional differences in native cardiac Ito . Abstract : This paper provides the first information on concentration‐dependent modulation of native cardiac transient outward current (I(to)) by the prototypic I(to) "activator", NS5806. In rabbit ventricular myocytes, a biphasic response was observed, with mixed activation, and inhibition at higher concentrations; in rabbit atrial myocytes the compound was actually an I(to) inhibitor. Our work shows that the compound may be useful for revealing regional differences in cardiac I(to).